Boundary layer flow and heat transfer of hybrid Cu-Al₂O₃/water nanofluid past a permeable surface - Khashi'ie, Najiyah Safwa (2020)
Hybrid nanofluid is invented to improve the heat transfer performance of traditional working fluids in many engineering and industrial applications. This thesis presents the numerical solutions and stability analysis of five problems related to the boundary layer flow with heat transfer in Cu-Al2O3/water hybrid nanofluid over different permeable surfaces. The five considered problems are (1) mixed convective stagnation point flow towards a vertical Riga plate, (2) magnetohydrodynamics (MHD) flow past a stretching/shrinking disc with Joule heating, (3) magnetohydrodynamics (MHD) flow past a stretching/shrinking cylinder with Joule heating, (4) three-dimensional flow past a stretching/shrinking sheet with velocity slip and convective boundary condition and (5) three-dimensional flow past a nonlinear stretching/ shrinking sheet with orthogonal surface shear. The combination of copper (Cu) and alumina (Al2O3) nanoparticles with water as the base fluid is modeled using the single phase model and modified thermophysical properties of nanofluid. A set of similarity transformation is opted to reduce the complexity of the governing model and then, computed using the bvp4c solver in the Matlab software. For all the problems, the validation of model are conducted by comparing the numerical values of present and previously published report in a specific case. The surfaces are permeable to allow the usage of suction parameter and generate the possible solutions. Dual solutions exist in all problems within a specified range of parameters, but it is found that only the first problem has dual solutions without the utilization of suction parameter. However, higher values of suction parameter can affect the performance of hybrid Cu-Al2O3/water nanofluid in augmenting the heat transfer rate as reported in second to fifth problems. Among all the parameters discussed in this thesis, copper volumetric concentration, electromagnetohydrodynamics (EMHD), magnetic, velocity slip and suction parameters can delay the boundary layer separation. Meanwhile, Biot number (convective condition), EMHD, suction, magnetic, velocity slip and nonlinear parameters have potential to increase the heat transfer rate of the hybrid nanofluid. Stability analysis proves that the first solution is more realistic than the second solution.